Identification and Characterization of a New Staphylococcal Enterotoxin-Related Putative Toxin Encoded by Two Kinds of Plasmids - Omoe, Katsuhiko (American Society for Microbiology, 2003)
We identified and characterized a novel staphylococcal enterotoxin-like putative toxin, which is named SER. Nucleotide sequencing analysis of the ser gene revealed that ser was most closely related to the seg gene. The ser gene product, SER, was successfully expressed as a recombinant protein in an Escherichia coli expression system, and recombinant SER (rSER) showed significant T-cell stimulation activity. The SER production in ser-harboring Staphylococcus aureus strains was confirmed by Western blot analysis using anti-rSER antibody. Moreover, ser was seen to be encoded by at least two types of plasmids. In particular, one kind of plasmid encoding the ser gene has been known as a sed- and sej-carrying pIB485-related plasmid.